Assessing the stationary energy storage equivalency of vehicle-to-grid charging battery electric vehicles. (1st July 2016) - Tarroja, Brian; Zhang, Li; Wifvat, Van; Shaffer, Brendan; Samuelsen, Scott
Abstract: A study has been performed to understand the quantitative impact of key differences between vehicle-to-grid and stationary energy storage systems on renewable utilization, greenhouse gas emissions, and balancing fleet operation, using California as the example. To simulate the combined electricity and light-duty transportation system, a detailed electric grid dispatch model (including stationary energy storage systems) was combined with an electric vehicle charging dispatch model that incorporates conventional smart and vehicle-to-grid capabilities. By subjecting smaller amounts of renewable energy to round-trip efficiency losses and thereby increasing the efficiency of renewable utilization, it was found that vehicle-to-grid energy storage can achieve higher renewable utilization levels and reduced greenhouse gas emissions compared to stationary energy storage systems. Vehicle-to-grid energy storage, however, is not as capable of balancing the power plant fleet compared to stationary energy storage systems due to the constraints of consumer travel patterns. The potential benefits of vehicle-to-grid are strongly dependent on the availability of charging infrastructure at both home and workplaces, with potential benefits being compromised with residential charging availability only. Overall, vehicle-to-grid energy storage can provide benefits over stationary energy storage depending on the system attribute selected for improvement, a finding amenable to managing through policy. Highlights: Using vehicle-to-grid-based storage increases the efficiency of renewable energy utilization. Vehicle-to-grid-based energy storage has less overall flexibility compared to stationary energy storage. The discharge ability of vehicle-to-grid-based provides a significant benefit over one-way smart charging. Both workplace and home charging are critical for providing vehicle-to-grid-related benefits. Increasing charging intelligence reduces stationary energy storage capacity requirements.